The impact of co-located NHS walk-in centres on emergency departments. Issue 4 (23rd March 2007) - Salisbury, Chris; Hollinghurst, Sandra; Montgomery, Alan; Cooke, Matthew; Munro, James; Sharp, Deborah; Chalder, Melanie
Abstract : Objectives: To determine the impact of establishing walk-in centres alongside emergency departments (EDs) on attendance rates, visit duration, process, costs and outcome of care. Methods: Eight hospitals with co-located EDs and walk-in centres were compared with eight matched EDs without walk-in centres. Site visits were conducted. Routine data about attendance numbers and use of resources were analysed. A random sample of records of patients attending before and after the opening of walk-in centres was also assessed. Patients who had not been admitted to hospital were sent a postal questionnaire. Results: At most sites, the walk-in centres did not have a distinct identity and there were few differences in the way services were provided compared with control sites. Overall, there was no evidence of an increase in attendance at sites with walk-in centres, but considerable variability across sites was found. The proportion of patients managed within the 4 h National Health Service target improved at sites both with and without walk-in centres. There was no evidence of any difference in reconsultation rates, costs of care or patient outcomes at sites with or without walk-in centres. Conclusions: Most hospitals in this study implemented the walk-in centre concept to a very limited extent. Consequently, there was no evidence of any effect on attendance rates, process, costs or outcome of care.